Themes and Messages Of Sketch Collection Goro-Goro Putu Wijaya - Lestari, Ria; Nuraeni Salsabila, Irma; Alifah, Nur (Riviera Publishing, 2022)
This research was motivated by the researcher's interest in social, cultural, political, and economic themes raised by the author. These themes were packaged attractively and loaded with life values that can be used as guidelines for readers. The problems discussed in this study related to the themes and messages contained in the 125 titles of sketches in Putu Wijaya's collection of Goro-Goro sketches. The purpose of this study was to describe the themes and messages in a collection of Goro-Goro sketches by Putu Wijaya. This study used a descriptive method, in the form of qualitative, with a structural approach. The source of this research data was a collection of Goro-Goro sketches by Putu Wijaya, the research data were quotes related to the themes and messages contained in the collection of Goro-Goro sketches by Putu Wijaya. The research data collection technique used in this research was a documentary study technique by examining literary works as a data source. Based on the results of data analysis, Putu Wijaya's collection of Goro-Goro sketches consisted of 51 social themed sketches, 58 political themed sketches, 12 cultural themed sketches, and 4 economic themed sketches. The theme of Putu Wijaya's collection of Goro-Goro sketches was closely related to his message, which was full of useful ideas, thought, and life values. Overall, the story contained in Putu Wijaya's collection of Goro-Goro sketches was true to its title—Goro-Goro which comes from the Javanese language, meaning chaos.